Determinants of Neonatal Hypothermia Among Babies Born in Public Hospitals of West Shewa Zone of Oromia Regional State, Ethiopia: Unmatched Case–Control Study - Seifu B; Belema D; Mamo K; Bulto GA (Dove Medical Press, 2021)
Benyam Seifu, Daniel Belema, Kassa Mamo, Gizachew Abdissa Bulto Department of Midwifery, College of Medicine and Health Sciences, Ambo University, Ambo, EthiopiaCorrespondence: Benyam Seifu Tel +251910451184Email benyamseifu77@gmail.comBackground: Neonatal hypothermia is one of the contributors to neonatal morbidity and mortality in Ethiopia. Even though the Oromia regional state is one of the regions with the highest neonatal-mortality rate in Ethiopia, only limited progress has been made towards understanding the determinant factors the causes of mortality such as neonatal hypothermia.Purpose: The study aims to identify determinants of hypothermia among newborns born in public health institutions.Methods: A hospital-based unmatched case–control study design was employed with a total of 226 (113 cases and 113 controls) babies born in public health facilities West Shewa Oromia region, 2019. The study participants were selected using systematic random sampling. Cases were babies with a temperature < 36.5°C and controls were babies with temperature ≥ 36.5°C measured at the axilla site using a digital thermometer at the first hour after delivery. The data were collected by interview and checklist using the CS-Entry and exported to SPSS version-23 for analysis. The data were collected from both the babies and their mothers. Binary and multiple logistic regressions were conducted to identify the determinants of hypothermia.Results: A total of 226 babies are participating in the study. Neonates who had not started early breastfeeding [AOR= 2.2, 95% CI (1.3, 4.1)], who had not skin-to-skin contact [AOR= 2.8, 95% CI (1.3, 6.6)] and babies with birth weight less than 2500 g [AOR=2.6, 95% CI (1.3, 5.2)] are found to be at higher risk of hypothermia.Conclusion and Recommendation: This study has found out that low birth weight babies and those who do not initiate breastfeeding and skin-to-skin contact at higher risk of hypothermia. These risk factors are previously identified by different studies; therefore, birth attendants should give due emphases to the immediate newborn cares in order to prevent neonatal hypothermia.Keywords: hypothermia, neonates, determinants, Ethiopia